The Influence of Hospital Brand Image, Health Service Quality and Patient Satisfaction on Loyalty at Arosuka Regional Hospital - Rindasiwi, Della Tamara; Tan, Pauline H. Pattyranie (GoAcademica Research & Publishing, 2024)
This study examines the relationships among hospital brand image, healthcare service quality, patient satisfaction, and patient loyalty. A cross-sectional quantitative approach was employed, utilizing questionnaires distributed to 160 respondents. The proposed model was tested using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings revealed significant and positive relationships between all variables, with the following results: brand image and loyalty (t-statistics 2.120, p-value 0.023 < 0.05), brand image and healthcare service quality (t-statistics 2.137, p-value 0.033 < 0.05), healthcare service quality and patient satisfaction (t-statistics 4.440, p-value 0.000 < 0.05), healthcare service quality and loyalty (t-statistics 2.472, p-value 0.014 < 0.05), and patient satisfaction and loyalty (t-statistics 7.448, p-value 0.000 < 0.05). The study highlights healthcare service quality and patient satisfaction as critical factors in enhancing patient loyalty. Therefore, hospitals are encouraged to continuously evaluate and improve their service quality to strengthen patient loyalty and maintain a competitive edge.